The Efforts of the Christian Religious Education Teacher in Using Short Film Audiovisual Media to Teach Grade V Students - Alpida Alpida; Prasetiawati Prasetiawati; Lukas Lukas (EDUJAVARE: International Journal of Educational Research, 2026)
This study aimed to describe the efforts of the Christian Religious Education teacher in using short-film audiovisual media to teach Grade V students at SDN 6 Pahandut and to identify the supporting and inhibiting factors influencing its implementation. The study employed a qualitative descriptive approach involving the Christian Religious Education teacher and Grade V students as research participants selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing, while the credibility of the findings was ensured through source and technique triangulation. The findings revealed that the teacher made systematic efforts by planning lessons carefully, selecting appropriate short-film audiovisual media, facilitating classroom discussions, encouraging student reflection, and relating biblical teachings to students' daily experiences. These instructional practices enhanced students' learning motivation, classroom participation, understanding of biblical values, and Christian character development. The study also identified several supporting factors, including the teacher's pedagogical competence, the availability of technological facilities, school support, collaborative professional practices, and students' enthusiasm for multimedia learning. The study concludes that the effective use of short-film audiovisual media in Christian Religious Education depends not only on the availability of technology but also on teachers' instructional competence, creativity, careful lesson planning, and continuous institutional support to create meaningful, student-centered, and technology-enhanced learning experiences.